Children's processing of emotion in ironic language - Nicholson, Andrew; Whalen, Juanita M.; Pexman, Penny M. (Frontiers in Psychology, 2013)
In the present study we addressed two novel questions: 1) is children’s irony appreciation and processing related to their empathy skills? and 2) is children’s processing of a speaker’s ironic meaning best explained by a modular or interactive theory? Participants were 31 8- and 9-year-old children. We used a variant of the visual world paradigm to assess children’s processing of ironic and literal evaluative remarks; in this paradigm children’s cognition is revealed through their actions and eye gaze. Results in this paradigm showed that children’s irony appreciation and processing were correlated with their empathy development, suggesting that empathy or emotional perspective taking may be important for development of irony comprehension. Further, children’s processing of irony was consistent with an interactive framework, in which children consider ironic meanings in the earliest moments, as speech unfolds. These results provide important new insights about development of this complex aspect of emotion recognition.